The Key Role of Menu Innovation: Optimizing Digital Marketing Performance in the Culinary Industry of South Tangerang, Banten Province - Munarsih, Munarsih; Aspiranti, Tasya; Amaliah, Ima; Nurhayati, Nunung; R. Oktini, Dede (International Journal of Science, Technology & Management, 2026)
Research Purpose this study seeks to thoroughly examine the implementation strategies behind Menu Innovation, outline approaches for Enhancing Digital Marketing Performance, and identify the essential role Menu Innovation plays in supporting such optimization within the culinary sector of South Tangerang (Tangsel), Banten Province. A Descriptive Qualitative method was applied, focusing on culinary SMEs operating in Tangsel. Data were gathered through in-depth interviews with business owners and marketing personnel, complemented by non-participant observation of digital content. Research Findings the qualitative results indicate that Menu Innovation is a central driver in improving digital performance. Its influence emerges through two primary mechanisms:(1) Menu Innovation is intentionally crafted as a visual asset that encourages the creation of User-Generated Content (UGC). Such content effectively boosts social-media engagement rates and organic visibility.(2) Menu Innovation offers an authentic storyline that strengthens digital storytelling efforts, enabling narrative transportation, which in turn has been shown to increase digital conversion rates (from viewers to online orders).